Ariel al trasluz de Cuba y Martí. Ariel against the light of Cuba and Martí. - Sánchez Aguilera, Osmar (Latinoamérica. Revista de Estudios Latinoamericanos, 2018)
En este artículo se pretende demostrar que el ensayo más famoso de Rodó tiene entre sus raíces más notables las cubanas, así en la dimensión política como en la cultural, y en su contenido tanto como en su circulación editorial. La correspondencia del escritor uruguayo con varios pares suyos de Cuba ofrece una mina de evidencias al respecto. Lugar especial entre esas raíces ocupa José Martí y particularmente quizá su ensayo “Nuestra América”. Abstract: This paper is intended to demonstrate that the most famous essay written by José Enrique Rodó has among its most noticeable roots the Cuban ones. This both in its political and cultural sides, as well as in its contents and circulation. The corpus of letters exchanged between the Uruguayan writer and his Cuban peers offers plenty of proofs about this. Special place among these is the influence of José Martí, mainly, maybe, his essay “Our America”.